2021
DOI: 10.1111/pai.13585
|View full text |Cite
|
Sign up to set email alerts
|

Virological and immunological features of SARS‐COV‐2 infected children with distinct symptomatology

Abstract: Background Although SARS‐CoV‐2 immunizations have started in most countries, children are not currently included in the vaccination programs; thus, it remains crucial to define their anti‐SARS‐CoV‐2 immune response in order to minimize the risk for other epidemic waves. This study sought to provide a description of the virology ad anti‐SARS‐CoV‐2 immunity in children with distinct symptomatology. Methods Between March and July 2020, we recruited 15 SARS‐CoV‐2 asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…For example, age-related decline and dysregulation of immune function, such as immunosenescence and inflammaging, can explain a gradient of severity of PASC as age increase ( 27 ). Also, younger children have more frequently an asymptomatic disease which, in previous studies, have been associated with lower virus load and faster virus clearance ( 28 , 29 ). This can support the hypothesis that asymptomatic children have lower risks of developing PASC, although in our study only 20 children were asymptomatic limiting the possibility of a statistical analyses aimed at defining this.…”
Section: Discussionmentioning
confidence: 91%
“…For example, age-related decline and dysregulation of immune function, such as immunosenescence and inflammaging, can explain a gradient of severity of PASC as age increase ( 27 ). Also, younger children have more frequently an asymptomatic disease which, in previous studies, have been associated with lower virus load and faster virus clearance ( 28 , 29 ). This can support the hypothesis that asymptomatic children have lower risks of developing PASC, although in our study only 20 children were asymptomatic limiting the possibility of a statistical analyses aimed at defining this.…”
Section: Discussionmentioning
confidence: 91%
“…Higher levels of activated CD4 and CD8 T cells were described in COVID-19 pediatric patients with MIS-C (22)(23)(24). COVID-19 children without or with mild/moderate clinical manifestations showed similar frequencies of activated CD4 and CD8 cells compared to age-matched control (15,22,25). In agreement with these findings, the present study found no differences between COVID-19 and non-COVID-19 children, and for the first time, we demonstrated that COVID-19 adults, mostly asymptomatic/mildly symptomatic, have a higher expression of both activated T and B cells, not only compared to non-COVID-19 adults but also compared to COVID-19 children.…”
Section: Differences Of Immunological Profile and Relationship With Prnt At Second Samplingmentioning
confidence: 85%
“…The data available in the pediatric population are controversial. Some studies found higher levels in symptomatic children compared to asymptomatic children (25,31), while other reports found no association of viral load and disease severity (5,32). A recent study, conducted in COVID-19 children within their first week from baseline (symptom onset and/or first positive virus detection) demonstrated an inverse relationship between viral load and nAbs, and the estimation of virus under curve from NPS, collected every 48 h up to undetectable viral load, confirmed the impact of nAbs on virus clearance (15).…”
Section: Differences Of Immunological Profile and Relationship With Prnt At Second Samplingmentioning
confidence: 99%
“…A number of recent studies have clarified that the COVID-19 clinical burden in children is mostly due to over-inflammation and immune cells dysregulation. 8 , 9 It must be noted that an apparently similar hyperinflammation status that characterizes severely ill COVID-19 adults could also be present in children. Critically ill children present with a pro-inflammatory syndrome characterized by a phenotypic picture resembling Kawasaki disease (KD) or toxic shock syndrome possibly related to COVID-19.…”
Section: Main Textmentioning
confidence: 99%